Lived Experiences Of Maternal Health Literacy Among Primigravida Women In Urban Indonesian Community: A Phenomenological Study - Gani, Nurul Fadhilah; Nurhidayah, Nurhidayah; Hasnah, Hasnah; Angelina, Annisa; S.Kadar, Kusrini; Seman, Nordianna (Alauddin Scientific Journal of Nursing, 2026)
Introduction: Maternal health literacy (MHL) is the ability of pregnant women to access, understand, and use health information during pregnancy. Despite various programs to reduce maternal mortality, limited maternal health literacy remains a challenge. This study aims to explore the experiences of primigravida pregnant women in understanding and utilizing health information during pregnancy in an urban Indonesian community. Methods: A qualitative study using a phenomenological design was conducted at the Kassi-Kassi Community Health Center in Makassar City. Six primigravida pregnant women were purposively selected. Data were collected through in-depth interviews and analyzed using the Colaizzi method. Results: Four main themes were identified: (1) limited understanding of maternal health literacy; (2) reliance on informal sources and digital media; (3) lack of knowledge about essential maternal health information; and (4) cultural influences and pregnancy myths. Conclusion: Maternal health literacy among primigravida pregnant women is influenced by limited understanding, the dominance of informal information sources, and culture. Contextual and culturally sensitive health education is needed to improve health decision-making during pregnancy